Children as community planners: embodied activities, visual-spatial thinking, and a re-imagined community. Issue 4 (3rd July 2020) - Bryant, Camille L.; Frazier, Andrea D.; Becker, Becky; Rees, Amanda
ABSTRACT: This qualitative research endeavor explored the role of embodiment as a pathway to visual-spatial thinking. The researchers relied on an interdisciplinary approach using geography and theater rooted in kinesthetic and empathetic embodied activities to facilitate visual-spatial thinking within the context of a community redevelopment project. The participants consisted of 14 elementary and middle school aged girls attending a Girls Inc. program within a low-income housing community. The researchers situated the findings using McCormack's ([1998. Visual/Spatial Thinking: An Essential Element of Elementary School Science . Washington, DC: Council for Elementary School Science]; [2011. "Don't Verbalize, Visualize!" NSTA WebNews Digest . Accessed June 15, 2016. http://www.nsta.org/publications/news/story.aspx?id=58298 ]) visual-spatial thinking typology and theories of embodiment. The findings revealed that the girls exhibited three types of visual-spatial thinking, which ranged from foundational to highly advanced ways of thinking about space, to include visual-spatial perception, memory, and creative thinking. The results also illustrate that embodied activities that engage sensorimotor functions through an interdisciplinary approach, can facilitate visual-spatial thinking.